Mapping a Teacher Questions in Teaching English at a Senior High School - Johannes Jefria Gultom; Maya Anggriani (BAHAS, 2021)
Abstract The objectives of this article are to identify and classify the questioning techniques (T) implemented by an English teacher in teaching English at a senior high school and to find out the cognitive levels of the questions (C) based on Bloom’s revised taxonomy. This article was based on a research conducted in a descriptive qualitative research design. The data were the 29 questions uttered by the teacher during a class meeting collected using documentation technique. There was 1 question which belonged to T1, 9 T2, 2 T3, 7 T4, 2 T5, 4 T6, 1 T7, and 13 T8. In addition, there were 20 questions which belonged to C1, 5 C2, 3 C4, and 1 C6.Keywords: Teacher Questions, Questioning Techniques, Bloom’s Revised Taxonomy